Gas Flaring and Hydrocarbon Pollutions in Selected Tropospheric Layers Of Niger Delta Basin Nigeria - Chukwudobe, Leo; Opara, Alexander Ihanyichukwu; Onyeuwaoma, Nnaemeka; Okereke, Chikwendu; Ibe, Francis; Emberga, Terhemba; Nkwoada, Amarachi Udoka; Okorondu, Ugochukwu; Echetama, Henry (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study analyzes spatiotemporal variations of atmospheric pollutants over the Niger Delta using two years of OMI and AIRS remote sensing data, supplemented by HYSPLIT source-sink modeling.
Keywords: aerosol; air pollution modeling; gas flaring; environmental contaminant; HYSPLIT; remote sensing